2017
DOI: 10.1007/s12603-016-0766-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary sodium intake and cognitive function in older adults

Abstract: OBJECTIVES To examine the association of dietary sodium intake with cognitive function in community-dwelling older adults. DESIGN Cross-sectional study SETTING Southern California community PARTICIPANTS White men (n=373) and women (n=552), aged 50–96 years from the Rancho Bernardo Study, a longitudinal study of cardiovascular disease risk factors and healthy aging. MEASUREMENTS During the 1992–1996 research clinic visit, a food frequency questionnaire was used to determine daily sodium intake; cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 45 publications
0
41
2
Order By: Relevance
“…The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers . Most of these studies (n = 40) found adverse effects of dietary salt on health outcomes and benefits of a sodium‐restricted diet on health, except for 7 that were neutral and one reported worsening symptoms with a sodium‐restricted diet in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers . Most of these studies (n = 40) found adverse effects of dietary salt on health outcomes and benefits of a sodium‐restricted diet on health, except for 7 that were neutral and one reported worsening symptoms with a sodium‐restricted diet in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…In addition, nuts and legumes are included as one component of the AHEI-2010 score, while these foods are considered separately in the aMed diet, lending them more weight. Furthermore, the sodium component, which is unique to the AHEI-2010 score, may partially mask associations as low sodium intake has previously been linked to lower cognitive function in the RBS cohort [ 47 ]. There is sparse literature examining the association between the AHEI-2010 diet and cognitive function [ 10 , 16 ] and no other study has had a follow-up of this length.…”
Section: Discussionmentioning
confidence: 99%
“…This review includes data from one clinical trial [27], six longitudinal cohort studies [28][29][30][31][32][33] (of which three studies only reported results of cross-sectional analyses [30,31,33]) and eight crosssectional studies [34][35][36][37][38][39][40][41] (Table 1). Six of the studies were conducted in the United States of America (USA) [27-29, 31, 32, 39], two studies were conducted in Australia [33,36], and one study each was conducted in Canada [30], Turkey [34], Korea [37], Poland [35], Scotland [38], Ireland [40], and China [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Mean age was 65.4 years (SD = 6.8) with a follow-up time of six months. The six [28][29][30][31][32][33] cohort studies had sample sizes ranging from 1,194 [29] to 6,426 [28] participants. Age ranged from 40 to 96 (only one study [32] included participants aged 40 years and above, with the mean age of participants higher than 45 years old).…”
Section: Study Characteristicsmentioning
confidence: 99%